Кон Dušan Kecmanović, Etnička vremena: Për Dušan Kecmanović, Etnička vremena - Naumovska, Senka; Ahmeti, Lindita (Identities: Journal for Politics, Gender and Culture, 2002)
Author(s): Senka Naumovska | Сенка Наумовска Title (Macedonian): Кон Dušan Kecmanović, Etnička vremena Title (Albanian): Për Dušan Kecmanović, Etnička vremena Translated by (Macedonian to Albanian): Lindita Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 2 (Winter 2002) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 189-190 Page Count: 2 Citation (Macedonian): Сенка Наумовска, „Кон Dušan Kecmanović, Etnička vremena“, Идентитети: списание за политика, род и култура, т. 1, бр. 2 (зима 2001): 189-190. Citation (Albanian): Senka Naumovska, „Për Dušan Kecmanović, Etnička vremena“, përkthim nga Maqedonishtja Lindita Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 2 (Winter 2002): 189-190.